VP16 targets an amino-terminal domain of HCF involved in cell cycle progression. - Wilson, A C (1997)
The herpes simplex virus (HSV) regulatory protein VP16 activates HSV immediate-early gene transcription through formation of a multiprotein-DNA complex on viral promoters that includes the preexisting nuclear proteins HCF and Oct-1. The HCF protein is a complex of amino- and carboxy-terminal polypeptides derived from a large (approximately 2,000-amino-acid) precursor by proteolytic processing. Here we show that a 361-residue amino-terminal region of HCF is sufficient to bind VP16, stabilize VP16-induced complex assembly with Oct-1 and DNA, and activate transcription in vivo. This VP16 interaction region contains six kelch-like repeats, a degenerate repeat motif that is likely to fold as a distinctive beta-propeller structure. The third HCF kelch repeat includes a proline residue (P134) that is mutated to serine in hamster tsBN67 cells, resulting in a temperature-sensitive defect in cell proliferation. This missense mutation also prevents direct association between HCF and VP16, suggesting that VP16 mimics a cellular factor required for cell proliferation. Rescue of the tsBN67 cell proliferation defect by HCF, however, requires both the VP16 interaction domain and an adjacent basic region, indicating that HCF utilizes multiple regions to promote cell cycle progression.